Tinjauan Literatur Sistematis tentang Total Productive Maintenance pada Industri - Yusrizal, Yusrizal; Rahmawati, Maharani; Febrian, Mohammad; Ramadhan, Syahrul; Alpiandi, Mohamad Kiki; Putra, Fibi Eko (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
Efforts to achieve the optimization of machine and equipment maintenance in manufacturing enterprises encounter a lot of problems, Because the output and production rate, quality, safety, and environment are almost entirely dependent on the conditions of the plant and equipment, Equipment losses such as adjustment, adjustment, stopping, and minor delays, defective products due to equipment, reduced machine speed, and decreased output have hampered their efforts to achieve a higher manufacturing level good. Japan's process industry introduced preventive maintenance (PM) early. This article discusses most of the Total Productive Maintenance (TPM) approaches in Enterprise Enterprises and provides an overview of the various TPM implementation practices that have been implemented. Based on the results of a review of 30 articles on TPM, it was found that most of the TPM implementations use the overall equipment effectiveness (OEE) parameter as the success rate of TPM implementation. And the article.